Pendidikan Inklusif dalam Perspektif Islam untuk Anak Usia Dini - Supriadi, Supriadi; Alensi, Debi; Asmara, Rika; Sari, Reni Aria; Helandri, Joni (STAI Bumi Silampari, 2024)
Inclusive education is a concept that is increasingly introduced into the global education system, particularly for early childhood. The goal of this concept is to provide equal opportunities for every child, including those with special needs, to develop in a supportive and diverse environment. In this context, inclusive education from an Islamic perspective holds significant relevance, as Islam emphasizes principles of equality, compassion, and respect for differences. However, while inclusive education has been widely discussed in academic circles, there is limited research focusing on the application of Islamic values in inclusive education for early childhood. Therefore, this study aims to analyze how Islamic principles can be applied in inclusive education for young children, with a focus on the values of compassion and respect for differences. This research adopts a library research method, analyzing various literature and previous studies related to inclusive education, Islamic education, and early childhood education. The data used consists of journal articles, books, and other relevant sources. Through the analysis of these sources, this study seeks to identify and develop an understanding of the role of Islamic education in creating an inclusive educational environment that supports the development of young children, including children with special needs. The findings of this study indicate that Islamic principles such as compassion (rahmah), brotherhood (ukhuwah), and equality (al-musawah) play a crucial role in supporting inclusive education for young children. These values can be applied in daily educational practices, both in teaching and in creating an inclusive school environment. Islam teaches to accept differences and respect every individual, so that children, including those with special needs, can learn in a mutually supportive and respectful atmosphere. Thus, inclusive education from an Islamic perspective can make a significant contribution to the character development and socio-emotional growth of young children.